Ethics, narratives and legitimacy in Defence acquisition - Newall, Paul John (Cranfield University, 2017)
Purpose: This research examines the proposition that ethics in business functions as part of legitimising narratives, rather than as a normative framework to guide or assess behaviour. Methodology: The applied ethics context of the acquisition of UK military capabilities is employed as a case study to test the proposition. Adopting a critical realist paradigm, Bourdieu’s theory of practice is applied in two stages. Quantitative (survey) and qualitative (narrative interview) data are collected, from which a Weberian ideal type is developed via narrative analysis. Findings: The results reveal that the public/private sector interface should be understood as a Bourdieusian practice, in which people use narratives involving normative ethical claims as a means of delegitimising options that threaten their field positions and capital accumulations. It is argued that akrasia – acting against one’s best interests – can be explained in these terms, and that even if a normative ethics of Defence acquisition is one day possible, any theory of ethics should – for completion – attempt to take account of how ethics serves to support or delegitimise specific narratives in the business of acquisition. Research limitations/implications: The research builds on the literature on akrasia, suggesting that the options available to people in business are behaviourally as well as cognitively limited. Moreover, potential codes of ethics are overruled by symbolic power within a practice and hence have no effect. The research is not longitudinal and is limited to a case study that necessarily involved unrepresentative populations, although the methodology facilitates generalisation. Further work on public/private sector interfaces is needed to explore how other populations narrate challenges to convention. Originality/value: The research represents a novel application of Bourdieu’s theory of practice to the context of public/private sector integration and uniquely to Defence acquisition, disputing the viability and utility of codes of ethics as part of professionalising the acquisition function. It also offers a sociological explanation of akrasia.